Modeling Land Use and Land Cover Changes and Their Effects on Biodiversity in Central Kalimantan, Indonesia - Sharma, R.; Nehren, U.; Rahman, S.A.; Meyer, M.; Rimal, B.; Seta, G.A.; Baral, H. (MDPI, 2018)
Land use and land cover (LULC) change causes biodiversity decline through loss, alteration, and fragmentation of habitats. There are uncertainties on how LULC will change in the future and the effect of such change on biodiversity. In this paper we applied the Land Change Modeler (LCM) and Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) Scenario Generator tool to develop three spatially explicit LULC future scenarios from 2015 to 2030 in the Pulang Pisau district of Central Kalimantan, Indonesia. The district is experiencing a rapid loss of biodiversity as a result of unprecedented LULC changes. Further, we used the InVEST Habitat Quality model to map habitat quality as a proxy to biodiversity in each of the scenarios. We find habitat quality decline is largest in a scenario where past trends of LULC change continue, followed by a scenario with planned agricultural expansion. Alternately, a conservation-oriented scenario results in significant improvements in habitat quality for biodiversity. This information can support in developing appropriate land use policy for biodiversity conservation in Indonesia.